Teaching and learning history: national and international perspectives - Ahsan, Abdullahil (2015)
Like all academic programs, teaching history at the university level has its own challenges. One major challenge in this regard originates from the perspective of the general orientation of the curriculum in which the subject is taught. One must note that history is the only social science subject that is taught at the secondary and high school level and this program of study is usually used for cultivating national identity and instilling loyalty to specific nations. This nationalist approach sometimes has created confusion particularly among Muslims due to the universal nature of the concept of ummah. This perplexity intensified in the 1990s with the rise of globalization in international politics. The clash of civilizations thesis complicated the question of identity and loyalty further. What is the impact of the nationalist approach of history curriculum on the discipline itself? This raises a fundamental question – what is the purpose history curriculum? Should the curriculum be used for indoctrinating students in favor of national interests? Or the curriculum is geared toward seeking the truth? Should the approach at the university level be different from the high school level? This paper addresses these questions.